Intra-abdominal foreign body as unexpected discovery mimicking suspicious malignancy. Issue 6 (23rd June 2021) - Kastiunig, Theresa; Sortino, Rosita; Vines, Larissa Clea; Benigno, Luca
Abstract: Although rare, postoperatively retained foreign bodies in the abdominal cavity still represent a serious issue for the surgical team as for the patients. Its clinical manifestation is often unspecific and the cases are therefore only irregularly registered. There are several known factors that increase the risk of retention of a foreign body, for example emergency surgeries, unplanned changes in procedure or a high body mass index. In this article, we would like to report the case of a male patient with a foreign body in the right lower quadrant after open appendectomy mimicking a tumor.